Analysis of the Current Personnel Situation in the Field of Science in Kazakhstan: Gender Aspect - D. M. Kangalakova; M. T. Satpayeva; S. Z. Ibraimova; N. N. Battalov (Экономика: стратегия и практика)
One of the main factors in the development of the state’s economy is science and innovation, namely human resources that realize these resources, with the help of high-quality scientists. In this regard, the purpose of the research article is to analyze the current state of personnel status in the field of science, identify gender characteristics, and give recommendations for improving personnel status. In the course of the study, an integrated approach was used, which included methods of analysis, synthesis, and comparative analysis. In addition, general scientific methods such as abstraction and deduction were used. As an information base, statistical data from the National Bureau of Statistics for the period 2018-2022 were used. In addition, the UN reports on science were used. In the course of the study, the results were obtained that there is a shortage of personnel in the field of science, a decrease in the number of scientists in technical specialties, low wages in this field, a small number of scientists with academic degrees, and gender inequality. To ensure economic development, it was proposed to rethink the education system and the field of science and the directions in which the problem of personnel in the field of science could be developed. The theoretical results of the study can be used in the continuation of research related to the personnel situation in the field of science. The results of the study can find practical application in reports, strategies and programs of government agencies.